THE INFLUENCE OF IMDb RATINGS FOR KKN FILM IN DANCING VILLAGE ON STUDENTS' WATCHING INTERESTS (STUDENTS OF STIKOM INTERSTUDI JAKARTA) - Aziz Bawazir, Lujain Abdul; Daniel, Mellisa Florentina (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Film is a work of art, audiovisual culture, film is a medium that can convey messages to society or a group of individuals can receive audiovisual communication through the use of film. Horror films in Indonesia were chosen as research objects because Indonesian audiences seem to enjoy getting their adrenaline pumping when watching horror films full of special effects, such as horror films with characters that are similar to figures from the invisible world, regardless of the good or bad quality of the horror film itself. This research focuses on the IMDb website because IMDb is the most famous film website, IMDb users in Indonesia reach 57 million people. This is proven by the many users who make IMDb useful for many people, especially for those who want to watch films. This research aims to find out whether there is a significant influence on the IMDb rating of the KKN film in Penari Village on interest in watching STIKOM InterStudi students. And find out how much influence ratings have on STIKOM InterStudy students' interest in watching. This research uses a quantitative approach with descriptive research type. This research uses 2 variables,namely the IMDb rating and interest in watching STIKOM InterStudi students from 2022-2023. The sampling technique uses non-probability sampling, namely purposive sampling. with a total sample of 90 Stikom interstudi students class 2022-2023. The data collection technique used was a questionnaire.